Benefits of Balloon‐Dilatable Bilateral Pulmonary Artery Banding in Patients With Hypoplastic Left Heart Syndrome and Other Complex Cardiac Anomalies. (8th December 2015) - Kise, Hiroaki; Suzuki, Shoji; Hoshiai, Minako; Toda, Takako; Koizumi, Keiichi; Hasebe, Yohei; Kono, Yosuke; Honda, Yoshihiro; Kaga, Shigeaki; Sugita, Kanji
Abstract : Objectives: The purpose of this study was to evaluate the potential of balloon‐dilatable bilateral pulmonary artery banding (b‐PAB) and its impact on the configuration of the pulmonary artery (PA). Background: We have previously used balloon‐dilatable b‐PAB as first‐stage palliation for patients with hypoplastic left heart syndrome (HLHS) and other complex cardiac anomalies. Methods: Two pliable tapes were placed around each branch of the PA and tightened with 7–0 polypropylene sutures in a manner that allowed for the subsequent adjustment of PA diameters. We retrospectively examined the adjustability of PA diameters by balloon dilation and the need for surgical PA angioplasty at later stages. Results: From January 2010 to October 2013, we performed b‐PAB in 8 patients, including 3 borderline cases between biventricular repair (BVR) and univentricular repair (UVR). The b‐PAB procedures were performed at a median age of 6.5 days (range, 2–10 days). Balloon dilations were performed in 10 lesions in 4 patients. All of the procedures were performed safely. Two patients reached definite BVR. The remaining 6 patients underwent open palliative procedures with univentricular physiologies that resulted in 2 deaths unrelated to the initial b‐PAB. In all but 1 of the patients, the PA configuration was properly maintained and did not require surgical pulmonary angioplasty. Conclusions: Balloon‐dilatable b‐PAB can be performed safely and prevents PA distortion at later stages. This technique should be considered for patients with complex cardiac anomalies if uncertainty exists regarding the optimal surgical strategy (BVR or UVR) in early infancy. (J Interven Cardiol 2015;28:594–599)